Reconstruction of Perineal Defects: A Comparison of the Myocutaneous Gracilis and the Gluteal Fold Flap in Interdisciplinary Anorectal Tumor Resection - Thiele, Jan R.; Weber, Janick; Neeff, Hannes P.; Manegold, Philipp; Fichtner-Feigl, Stefan; Stark, G. B.; Eisenhardt, Steffen U. (Frontiers in Oncology, 2020)
Resection of anorectal malignancies may result in extensive perineal/pelvic defects that require an interdisciplinary surgical approach involving reconstructive surgery. The myocutaneous gracilis flap (MGF) and the gluteal fold flap (GFF) are common options for defect coverage in this area. Here we report our experience with the MGF/GFF and compare the outcome regarding clinical key parameters. In a retrospective chart review, we collected data from the Department of Plastic Surgery of the University of Freiburg from December 2008–18 focusing on epidemiological, oncological, and therapy-related data including comorbidities (ASA Classification) and peri-/postoperative complications (Clavien-Dindo-System). 29 patients were included with a mean follow-up of 17 months. Of the cases, 19 (65.5%) presented with recurrent disease, 21 (72.4%) received radiochemotherapy preoperatively, 2 (6.9%) received chemotherapy alone. Microscopic tumor free margins were achieved in 25 cases (86.2%). 17 patients (7 men, 10 women, rectal adenocarcinoma n=11; anal squamous cell carcinoma n=6; mean age 58.5±10.68, mean BMI 23.1, mean ASA score 2.8) received a MGF (unilateral n=10; bilateral n=7). 12 patients (7 men, 5 women, rectal adenocarcinoma n=7; anal squamous cell carcinoma n=4, proctodeal gland carcinoma n=1, mean age 66.2±9.2, mean BMI 23.6, mean ASA score 2.6) received coverage with a GFF (unilateral n=4; bilateral n=8). Mean operation time of coverage was 105±9 minutes for unilateral and 163±11 for bilateral MGFs, 70±13 minutes for unilateral and 107±14 for bilateral GFFs. Complications affected 62%. There was no significant difference in the complication rate between the MGF- and GFF-group. Complications were mainly wound healing disorders that did not extend the hospital stay. No flap loss and no complication that lead to long-lasting disability was documented (both groups). Pain-free sitting took more time in the GFF-group due to the location of the donor site. MG-flaps and GF-flaps prove to be reliable and robust techniques for perineal/pelvic reconstruction. Though flap elevation is significantly faster for GF-flaps, preoperative planning and intraoperative Doppler confirmation are mandatory. With comparable complication rates, we suggest a decision-making based on distribution of adipose tissue for dead space obliteration, intraoperative patient positioning, and perforator vessel quality/distribution.